Calculation of the Operation Parameters of the Catalytic Converters of the Harmful Gas Impurities - Ved, V. E.; Krasnokutskiy, E. V.; Satayev, M. I.; Ved, A. V.; Saipov, A. A. (The Italian Association of Chemical Engineering, 2016)
There are theoretically founded principles of catalytic converters designing of harmful gas emissions of various heat devices. Experimental investigations have shown that the smallest aerodynamic losses in the constructions of gas neutralizers are achieved at the using of profiled ceramic blades as working units - carriers of catalysts. To ensure intensive mixing of the flow inside the converter the input edges of the blades grids of the future stages should be located between the output edges of the blades of the grids of the preceding stages.